The Influence of Work Conflict, Leadership, Work Stress, Workload, and Interpersonal Communication on Employee Performance at PT BPR Nusamba Rambipuji Jember: English - Lucky Ambarwati; Haifa; Muhdar (Yayasan Pendidikan Belajar Berdikari, 2025)
This study aims to determine and analyze the influence of work conflict, leadership, Work stress, work load, interpersonal communication on employee performance at PT BPR Nusamba Rambipuji, Jember The research method used is quantitative. The sample of this study was 66 people, using saturated sample technique. In this study, data was collected with observations, interviews, literature review and questionnaires. The analysis used includes data instrument tests (validity test and reliability test), multiple linear regression analysis, classical assumption test (normality test, multicollinearity test, heterokedasticity test), and hypothesis test (F test, t test, and determination coefficient test). Based on the result of the analysis, this study shows that the F test of the variables of work conflict, leadership, work stress, work load, interpersonal communication had a simultaneous effect on employee performance. Meanwhile, the results of the t-test research in this study showed that the variables of interpersonal communication had a positive and significant effect on employee performance, while the variables of work conflict , leadership, work stress, workload had no significant effect on employee performance.